Case Study: Feather Follicle Cyst in a Blue-and-Yellow Macaw (Ara ararauna) - Rafif Galih Satria; Ira Sari Yudaniayanti; Bambang Sektiari Lukiswanto (Universitas Airlangga, 2026)
Feather follicle cysts are integumentary disorders commonly observed in psittacine birds and are frequently associated with repetitive mechanical trauma or abnormal feather growth. This case study aimed to describe the clinical findings, diagnostic workup, and surgical management of a feather follicle cyst in a one-year-old blue-and-yellow macaw (Ara ararauna) treated at the Rumah Sakit Hewan Pendidikan Universitas Airlangga. The bird presented with a three-week history of progressive, oval-shaped swelling on the left wing following repetitive self-inflicted feather damage. Trauma was the suspected, although not definitively confirmed, primary predisposing factor based on the clinical history of feather-destructive behavior and prior veterinary-supervised feather plucking. Surgical excision was performed under local anesthesia using lidocaine infiltration (2%, 2 mg/kg), and the excised tissue was submitted for histopathological examination, which confirmed the diagnosis. The surgical site was closed using absorbable polyglycolic acid (PGA) sutures. Postoperative management included intramuscular ampicillin sodium (Viccillin®, 10–20 mg/kg, q12h, for 7 days), intramuscular diphenhydramine HCl (Recodryl®, 2–4 mg/kg, q12h, for 3 days), intramuscular dexamethasone (0.5–1 mg/kg, q24h, for 3 days), and oral vitamin supplementation (Neurobion® and Sangobion®). Progressive clinical improvement was observed during a structured four-week follow-up period, with complete wound healing by week three, early feather regrowth at four weeks, and no recurrence at eight weeks post-surgery. This case highlights the importance of systematic differential diagnosis, histopathological confirmation, and the combination of surgical excision with multimodal pharmacological management in young psittacines presenting with wing-associated feather follicle cysts in a Southeast Asian clinical setting.